G107 How do you help your unwell child? A sequential simulationTM project. (May 2019) - Coughlan, C; Imran, A; Holden, B; Weldon, S; Kneebone, R; Bello, F; Blair, M; Watson, M
Abstract : Introduction: Paediatric emergency department attendances are increasing nationwide, with almost 25% of cases deemed 'avoidable'. 1 Emergent strategies look to 'nudge' patients towards appropriate healthcare services. Sequential Simulation TM (SqS) is a novel technique that aims to portray a patient's 'journey' in a compressed live performance involving actors and healthcare professionals. In addition to other applications, SqS can be used to understand patient and carer behaviours; identify areas for improvement within existing pathways; and involve patients in service co-design. Methods: An SqS design was formulated after consultation with NHS 111 and two patient groups. Semi-structured interviews were conducted with 20 families at a community centre, and a separate meeting held with a local Somali Women's Group. Interviews were transcribed and subjected to thematic content analysis. The resulting performance explored the experiences of a new mother in accessing healthcare services in Urgent Care Centre, General Practice (GP) and Community Pharmacy settings. The event took place at a community centre and was attended by 21 local families and 18 health professionals. Layperson participants were separated into three groups with dedicated facilitators who led discussion of three questions posed after the performance: How did the simulation make you feel? How did the simulation make you feel? How did the simulation compare to your own experience? Answers were recorded and facilitators took written field notes during the discussion. All participants were asked to complete an end-of-simulation questionnaire. Results: Participants identified three major issues which influenced their decision-making when seeking help for their unwell child – operating hours of GP surgeries, accessing GP appointments in-hours, and language barriers. Participants also reported inconsistent delivery of key information by health professionals, which often led them to seek a second opinion. Suggested solutions included provision of classes for new parents in local community centres; improved access to a named GP to provide continuity of care; and raising awareness of the roles that pharmacists can play in managing minor childhood illnesses. Conclusion: SqS is a novel technique which facilitates access to hard-to-reach patient groups, provides rich qualitative data, and enables robust patient engagement. Reference: National Audit Office. Reducing emergency admissions 2018. doi: https://www.nao.org.uk/report/reducing-emergency-admissions/